2022
DOI: 10.3390/admsci12040176
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Business Environment for Entrepreneurial Motivation

Abstract: The influences of personality traits and business barriers on entrepreneurial behaviour have been studied by numerous researchers. However, the mechanisms by which changes in institutional contexts and personality traits affect individuals’ entrepreneurial motivation have not received enough attention from researchers. This paper aims to fill this gap in the literature by examining the joint effects of personality traits and business barriers on one’s motivation to engage in entrepreneurial activity. A structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 79 publications
0
0
0
Order By: Relevance
“…Such a relationship, particularly based on the long-term perspective, has attracted a lot of interest. In the majority of consulted research pieces, this fact is strongly highlighted; being argued that the relationship represents a great source for developing competitive advantage for both parties (Dwyer et al 1987;Janda et al 2002;Lambe et al 2002;Wong et al 2005;Tarí et al 2020;Dvorský et al 2021;Zarnadze et al 2022). Within the scholarly discourse, a consensus appears to hold sway among researchers on the fact that farmers are facing a very dynamic environment nowadays, which encompasses changes in technology, climate, market prices, as well as institutional and political changes, leading to the need for farmers to adapt as soon as possible (Ihli et al 2014;Skreli et al 2015;Evteeva et al 2019;.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such a relationship, particularly based on the long-term perspective, has attracted a lot of interest. In the majority of consulted research pieces, this fact is strongly highlighted; being argued that the relationship represents a great source for developing competitive advantage for both parties (Dwyer et al 1987;Janda et al 2002;Lambe et al 2002;Wong et al 2005;Tarí et al 2020;Dvorský et al 2021;Zarnadze et al 2022). Within the scholarly discourse, a consensus appears to hold sway among researchers on the fact that farmers are facing a very dynamic environment nowadays, which encompasses changes in technology, climate, market prices, as well as institutional and political changes, leading to the need for farmers to adapt as soon as possible (Ihli et al 2014;Skreli et al 2015;Evteeva et al 2019;.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was also reported that entrepreneurship education moderates the relationship between supportive environment and entrepreneurial intention. Zarnadze et al (2022) and Salisu, et al (2022) investigated relationship between personality attributes and entrepreneurial intention.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The key person who runs SMEs is the owner/entrepreneur, unlike in large firms where the group of key people takes strategic decisions among top management. Since SMEs are managed and controlled by owners or entrepreneurs, a lot depends on how owners and managers manage and plan their business (Dvorský et al, 2021;Khan et al, 2020;Zarnadze et al, 2022). Hence, the behavioural part of the owner and entrepreneurs cannot be ignoredspecifically, their psychological motivation.…”
Section: Psychological Motives/motivation and Business Recoverymentioning
confidence: 99%